Kewenangan Dewan Keamanan Menghentikan Yurisdiksi ICC : Studi Kasus Resolusi Dewan Keamanan Nomor 1497 Tahun 2003 - Author: Sefriani (Fakultas Hukum Universitas Islam Indonesia, 2009)
Though Security Council of the United Nations is a permanent organ within the UN, but this organ is out of the Roma Statute of 1998 coverage. As such, the Security Council in not of the possession of the right to amend the section 16 of the Roma Statute of 1998 which eliminate the jurisdiction of ICC on the UN troops who are the citizen of non state party in the Roma Statute of 1990.Keywords: Keywords: International Criminal Court, Security Council’s Resolution no. 1497 of 2003